2019
DOI: 10.1186/s12935-019-0950-7
|View full text |Cite
|
Sign up to set email alerts
|

A six-gene prognostic model predicts overall survival in bladder cancer patients

Abstract: Background The fatality and recurrence rates of bladder cancer (BC) have progressively increased. DNA methylation is an influential regulator associated with gene transcription in the pathogenesis of BC. We describe a comprehensive epigenetic study performed to analyse DNA methylation-driven genes in BC. Methods Data related to DNA methylation, the gene transcriptome and survival in BC were downloaded from The Cancer Genome Atlas (TCGA). MethylMix was used to detect BC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 40 publications
(43 reference statements)
0
42
0
Order By: Relevance
“…The ROC curve analysis, C-index, calibration curves, and DCA con rmed the model's predictive power. Compared to models based on other sequencing data, the prognostic model constructed by immune-related lncRNAs presented better e cacy according to ROC curve method [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The ROC curve analysis, C-index, calibration curves, and DCA con rmed the model's predictive power. Compared to models based on other sequencing data, the prognostic model constructed by immune-related lncRNAs presented better e cacy according to ROC curve method [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer is a heterogeneous disease with a high incidence and recurrence rate, but there is no robust predictive tool to guide clinical treatment [5]. Some recent studies have also constructed a new model for bladder cancer, such as DNA methylation-driven genes related model [23] and immune genes related model [24]. These models prefer to take a kind of gene set to build the model, rather than the whole genome into the screening.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that ARL14 silencing in lung cancer cells blocks ERK1/2 and p28 signaling and upregulates the cell death inducing DFFA-like effector C (CIDEC), leading to cell cycle arrest (Guo et al, 2019). Also, hypermethylation of ARL14 was found to be correlated with a poor prognosis of bladder cancer patients (Wang L. et al, 2019).…”
Section: Arl5 Arl6 Arl8 Arl14 and Arfrp1mentioning
confidence: 99%